Prevalence and Social Acceptability of Cannabis, Tobacco, and Alcohol Use in Adult Women - Patricia Coughenour; Jaclyn S. Sadicario; Nicole Karjane; Anna Beth Parlier-Ahmad; Lisa Phipps; Dace S. Svikis (Women's Health Reports, 2021)
Background: As more US states legalize cannabis use, prevalence of use continues to rise and attitudes toward use are changing. This study examined (1) the relationship between cannabis use and social acceptability of use and (2) how social acceptability and use of cannabis relate to anxiety, depression, and several pain conditions. Materials and Methods: Participants were n?=?210 nonpregnant women recruited from two women's health clinics for an anonymous survey of complementary and integrative health practices. Survey domains included demographics, recent and lifetime cannabis, cigarette, and alcohol use, depression, anxiety, pain, and social acceptability of substances studied. Results: The sample had a mean age of 38.7 years and was 50.0% Black. Approximately 12.9% of the sample endorsed recent cannabis use, 17.2% endorsed recent cigarette use, and 57.5% endorsed recent alcohol use. Acceptability of use varied by substance. One-third (33.3%) of women found cannabis use to be socially acceptable. Higher social acceptability scores for cannabis were correlated with higher acceptability scores for each of the other substances studied, with the strongest correlation for e-cigarettes (R2 of 0.395, p?<?0.001) and the weakest for alcohol (R2 of 0.296, p?<?0.001). Women reporting anxiety (38.9%) and recent acute pain (28.6%) rated cannabis use as more socially acceptable than those without such symptoms. Conclusions: Women with recent cannabis use were more likely to find use of alcohol, tobacco, and cannabis to be socially acceptable than those not reporting cannabis use. More research is needed to better understand these relationships, as they might help to identify opportunities for education and intervention in this population.